2018
DOI: 10.1002/2017je005358
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of Lithospheric Flexure and Elevated Heat Flow in Stereo Topography at Coronae on Venus

Abstract: Signatures of lithospheric flexure were previously identified at a dozen or more large coronae on Venus. Thin plate models fit to topographic profiles return elastic parameters, allowing derivation of mechanical thickness and surface heat flows given an assumed yield strength envelope. However, the low resolution of altimetry data from the NASA Magellan mission has hindered studying the vast majority of coronae, particularly those less than a few hundred kilometers in diameter. Here we search for flexural sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 58 publications
2
48
1
Order By: Relevance
“…Venus currently shows no clear evidence of Earth‐like plate tectonic activity (e.g ., Schubert et al, ; Solomon et al, ). However, analysis of gravity and topography observations requires active mantle convection upwelling beneath large volcanic rises such as Beta, Atla, and Eistla Regiones, the Devana Chasma rift, and some coronae (Grimm et al, ; Kiefer & Hager, ; Kiefer & Peterson, ; O'Rourke & Smrekar, ; Simons et al, ; Smrekar et al, ; Smrekar & Stofan, ). Tectonic observations of Venus indicate only limited recent surface motions, for example only 10‐20 km of extension at Devana Chasma ( Connors & Suppe, ; Kiefer & Swafford, ; Rathbun et al, ; Solomon et al, ), which is similar to the extension at continental rifts on Earth (see Table 2 of Kiefer & Swafford, ).…”
Section: Introductionmentioning
confidence: 99%
“…Venus currently shows no clear evidence of Earth‐like plate tectonic activity (e.g ., Schubert et al, ; Solomon et al, ). However, analysis of gravity and topography observations requires active mantle convection upwelling beneath large volcanic rises such as Beta, Atla, and Eistla Regiones, the Devana Chasma rift, and some coronae (Grimm et al, ; Kiefer & Hager, ; Kiefer & Peterson, ; O'Rourke & Smrekar, ; Simons et al, ; Smrekar et al, ; Smrekar & Stofan, ). Tectonic observations of Venus indicate only limited recent surface motions, for example only 10‐20 km of extension at Devana Chasma ( Connors & Suppe, ; Kiefer & Swafford, ; Rathbun et al, ; Solomon et al, ), which is similar to the extension at continental rifts on Earth (see Table 2 of Kiefer & Swafford, ).…”
Section: Introductionmentioning
confidence: 99%
“…The Nar Sulcus fractures (Figure 1), which are centrally located at 280.11°E, 41.86°S within the Yalode impact crater, display morphologies similar to those of imbricated listric normal faults on the Earth and have topographic profiles suggestive of elastic flexure. Estimates of these parameters through the analysis of flexurally supported topography have previously been done on the Earth (e.g., Kusznir et al, 1991;Lowry & Smith, 1994;Weissel & Karner, 1989), Venus, (e.g., O'Rourke & Smrekar, 2018), Mars (e.g., Grott et al, 2005;Ruiz et al, 2006), Ganymede (Nimmo & Pappalardo, 2004;Nimmo et al, 2002), Europa (Nimmo & Schenk, 2006;Ruiz, 2005), Tethys (Giese et al, 2007), and Enceladus (Giese et al, 2008). When this elastic thickness is combined with an assumed strength profile and strain rate, the mechanical thickness and heat flux present at the site of the newly formed topography can be estimated.…”
Section: Introductionmentioning
confidence: 99%
“…When this elastic thickness is combined with an assumed strength profile and strain rate, the mechanical thickness and heat flux present at the site of the newly formed topography can be estimated. Estimates of these parameters through the analysis of flexurally supported topography have previously been done on the Earth (e.g., Kusznir et al, 1991;Lowry & Smith, 1994;Weissel & Karner, 1989), Venus, (e.g., O'Rourke & Smrekar, 2018), Mars (e.g., Grott et al, 2005;Ruiz et al, 2006), Ganymede (Nimmo & Pappalardo, 2004;Nimmo et al, 2002), Europa (Nimmo & Schenk, 2006;Ruiz, 2005), Tethys (Giese et al, 2007), and Enceladus (Giese et al, 2008). Despite a plethora of evidence suggesting Ceres' upper layer is rich in water ice (e.g., Buczkowski et al, 2016;Combe et al, 2016Combe et al, , 2019Fu et al, 2017;Hughson et al, 2018;Prettyman et al, 2017;Schmidt et al, 2017;Sizemore et al, 2017Sizemore et al, , 2018, its exact concentration and HUGHSON ET AL.…”
Section: Introductionmentioning
confidence: 99%
“…The curve‐fitting algorithm returns formal uncertainties for all parameters. O'Rourke and Smrekar (2018) used a sophisticated Markov chain Monte Carlo to fit flexural models to topography, but also demonstrated that simpler curve‐fitting algorithms yield equivalent results. We use a Monte Carlo method to propagate the uncertainties on α to estimate the “1‐sigma” uncertainties on the best‐fit elastic thickness.…”
Section: Methodsmentioning
confidence: 99%